Integrative Medicine in J&K: Opportunities and Challenges - Singh, Mohan; Gupta, Arun; Charak, Sandeep (International Research Journal of Ayurveda & Yoga, 2022)
India, the cradle of civilization has always been an epicenter of medical pluralism. India gifted the world with some of the popular health care systems which includes Ayurveda, Yoga and Siddha and disciplines of Unani and Sowa Rigpa (Amchi). These organized systems of health care evolved on this great land to be propagated all across the world. The beauty of medical pluralism is that these systems have so deeply in grained in the Indian culture that even after the wider popularization of western biomedical medicine, a great proportion of Indian population seek health care from these systems of medicine vis a vis biochemical medicine which laid the foundation of integrative medicine in India. In recent years, with the increasing burden of communicable and non communicable diseases, health care policy makers have realized that a single system of health care is not sufficient to provide holistic health and cater the health needs of an individual or a community, which changed the focus of health care policy makers to look towards the idea of integrative medicine. In the recent years, due to emergence of Covid-19 pandemic, the global upsurge of utilization of Ayush and Complementary and Alternative interventions for prevention and management of Covid-19 has been registered. Public health agencies in India promoted the use of integrated medical interventions in order to tackle this global health problem when there was no vaccine on the horizon. Patients and physicians worldwide use integrative medicine for the management of Non communicable diseases in order to reverse it or stop its